Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Math 9

Download as pdf or txt
Download as pdf or txt
You are on page 1of 7

9

Division of Negros Occidental

Mathematics
QUARTER 1 – MODULE 4
Solves Equations Transformable into Quadratic Equations
(Including Rational Algebraic Expressions)
M9AL-Ic-d-1

Development Team of the Module

Writer: LILIBETH G. GATOC


Editors: Jenny G. Ruales and Irwin V. Singson

Reviewers: Ma. Teresa F. Mijares, EPS and Mitchelle A. Casiple


QUARTER 1

TOPIC: EQUATIONS TRANSFORMABLE INTO QUADRATIC EQUATIONS

Task Analysis:
Solving Rational Algebraic Equations Transformable into Quadratic Equations
(Including Rational Algebraic Expressions)
(M9AL-Ic-d-1)

Sub - Topics:
 Solving Quadratic Equations that are NOT Written in Standard Form
 Solving Rational Algebraic Equations Transformable into Quadratic Equations

GUIDE CARD:
Good day! Now that we can solve all quadratic
equations we want to solve equations that are
not exactly quadratic but can either be made to
look quadratic or generate quadratic equations.
HOW???
We start with the former.

Are you ready??? First we will tackle


about equations NOT in standard form
and after that you’ve master that we will
try to transform Rational Equations.
Okay! Let’s start!!!

EXAMPLES:

“Solving Quadratic Equations NOT written in Standard Form”

1. Find the solution of x2 + 2x = -1

x2 + 2x = -1 Equation

x2 + 2x + 1 = 0 Write the above quadratic equation with right


side equal to 0.
(x + 1)2 = 0 Factor the equation.
x = -1 Solve the equation to obtain the repeated
solution.
2. Solve x(x-5)=36

x(x-5)=36 Equation

x(x-5)=36 x2 - 5x = 36 Simplify the expression

x2 - 5x = 36 x2 - 5x - 36 = 0 Write in standard form

Use any methods in solving quadratic


equations to find the solution
x2 - 5x - 36 = 0

x2 - 5x - 36 = 0 We use factoring
(x - 9) ( x + 4 ) = 0
x- 9 = 0 or x + 4 = 0
x=9 x = -4

x(x-5)=36 Check whether the obtained values of x


makes the equation x(x-5)=36 true.
If x=9 if x = -4
9(9-5) = 36 -4(-4-5) = 36
9(4) = 36 -4(-9) = 36
36 = 36 36 = 36

3. Find the roots of the equation (x+5)2 + (x-2)2 = 37

(x+5)2 + (x-2)2 = 37 Equation

(x+5)2 + (x-2)2 = 37 Simplify the expression and


combine like terms
x2 + 10x +25 + x2 - 4x + 4 = 37
2x2 + 6x + 29 = 37

2x2 + 6x + 29 = 37 2x2 + 6x + 29 - 37 = 37 - 37 Write in standard form


2x2 + 6x - 8 = 0

Use any methods in solving


quadratic equations to find the
2x2 + 6x - 8 = 0
solution

2x2 + 6x - 8 = 0 We use factoring


(2x - 2)(x + 4) = 0

2x - 2 =0 x+4=0
2x - 2 + 2 = 0 + 2 x+4-4=0-4
2x = 2 x = -4
x=1

(x+5)2 + (x-2)2 = 37 Check whether the obtained values of


x makes the equation x(x-5)=36 true.
Ifx=1 if x = -4
(1+5)2 + (1-2)2 = 37 (-4+5)2 + (-4-2)2 = 37
(6)2+(-1)2=37 (1)2 + (-6)2 = 37
36+1=37 1 + 36 = 37
37=37 37 = 37

“Solving Rational Algebraic Equations Transformable into Quadratic Equations”

6 𝑥−3
1. Solve the rational algebraic equation + =2
𝑥 4
6 𝑥−3 Equation
+ =2
𝑥 4

6 𝑥−3 6 𝑥−3
+ =2 4𝑥 ( + ) = 4𝑥(2) Multiply both sides of the equation by
𝑥 4 𝑥 4
the Least Common Multiple (LCM) of all
24 + 𝑥 2 − 3𝑥 = 8𝑥 denominators. In the given equation,
the LCM 4𝑥.
24 + 𝑥 2 − 3𝑥 = 8𝑥 x2 - 3x - 8x + 24 = 8x - 8x Write the resulting quadratic equation
𝑥 2 − 11𝑥 + 24 = 0 in standard form

𝑥 2 − 11𝑥 + 24 = 0 Find the roots of the resulting equation


(𝑥 − 3)(𝑥 − 8) = 0 using any of the methods of solving
quadratic equation. Try factoring in finding
𝑥−3=0 or 𝑥−8=0 the roots of the equation.
𝑥=3 or 𝑥=8
6 𝑥−3 Check whether the obtained values of 𝑥
+ =2 6 𝑥−3
𝑥 4 make the equation 𝑥 + 4 = 2 true.

If x = 3 if x = 8
6 𝑥−3 6 𝑥−3
+ =2 + =2
𝑥 4 𝑥 4
6 33
 2 6

83
2
3 4 8 4
0 6 5
2  2  2
4 8 4
6 5
20  2 8(  )  (8) 2
8 4
22 6  ( 2)(5)  16
6  10  16
16  16
8 4𝑥
2. Example 2: Find the roots of 𝑥 + =1+
𝑥−2 𝑥−2
8 4𝑥
The equation 𝑥 + =1+ is a rational algebraic equation that can be written in the form of 𝑎𝑥 2 + 𝑏𝑥 + 𝑐 = 0.
𝑥−2 𝑥−2
To find the roots of the equation, you can follow the same procedure as in the previous example of solving rational algebraic
expression.
8 4𝑥 Equation
𝑥+ =1+
𝑥−2 𝑥−2
8 4𝑥 8 4𝑥
𝑥+ =1+ 𝑥 − 2 (𝑥 + ) = (𝑥 − 2) (1 + ) Multiply both sides of the equation by the
𝑥−2 𝑥−2 𝑥−2 𝑥−2
LCM of all denominators. In the given
equation, the LCM is 𝑥 − 2
(x-2)(x) + 8 = (x-2) + 4x write the resulting quadratic equation in a
𝑥 2 − 2𝑥 + 8 = 𝑥 − 2 + 4𝑥 standard form
𝑥 2 − 2𝑥 + 8 = 5𝑥 − 2
2
x - 5x - 2x + 8 +2 = 0
𝑥 2 + 7𝑥 + 10 = 0
2 Find the roots of the resulting equation
𝑥 + 7𝑥 + 10 = 0
(𝑥 − 5)(𝑥 − 2) = 0 using any of the methods of solving
𝑥−5=0 or 𝑥−2=0 quadratic equations. Let us solve the
x-5+5=0+5 x-2+2=0+2 equation by factoring.
𝑥=5 or 𝑥=2
For 𝑥 = 5 Check whether the obtained values of 𝑥
8 4𝑥
8 4𝑥 make the equation 𝑥 + =1+ true.
𝑥−2 𝑥−2
𝑥+ =1+
𝑥−2 𝑥−2
8 4(5) Hence, 𝑥 = 5 is a solution.
5+ =1+
5−2 5−2
8 20
5+ =1+
3 3
15 + 8 3 + 20
=
3 3
23 23
=
3 3
8 4𝑥 Observe that at 𝑥 = 2, the value of
8
is
𝑥+ =1+ 𝑥−2
𝑥−2 𝑥−2 undefined or does not exist. The same is true
8 4( 2) 4𝑥
2  1 with
𝑥−2
. Hence, 𝑥 = 2 is an extraneous root or
22 22 solution of the equation 𝑥 +
8
= 1+
4𝑥
.
𝑥−2 𝑥−2
8 8
2   1 An extraneous root or solution is a solution of
0 0 an equation derive from an original equation.
However, it is not a solution of the original
equation.

Activity 1: ACTIVITY TIME!!!


Let’s Recall!!!
Find the solutions of the quadratic equations.
1. x2 - 4x + 4 = 0
2. s2 - 3s - 10 = 0
3. r2 + 5r - 14 = 0
4. 2m2 + 5m + 2 =0
5. 3p2 + 7p + 4 = 0
Activity 2:
Let’s Add and Subtract!
Find the sum and difference of the following equations.

1 2x x 1 x  2
1.  4. 
x 5 2x 3x

4 2x 1 x  5 x 1
2.  5. 
x 5 2x x2
2x x 1
3. 
3 x

ASSESSMENT:
Let’s Be True!
Find the solution set of the following.
1. x (x+3) = 28
2. 3s (s - 2) = 12s
3. (t + 1)2 + (t - 8)2 = 45
4 t
4.   2
t 3 2
2s 1
5.  3
x 5 x 3

ENRICHMENT:
Read and understand the situation below, then answer the questions that follow.
Jessie and Mark are planning to paint a house together. Jessie thinks that if he works alone, it
would take him 5 hours more than the time Mark takes to paint the entire house. Working together,
they can complete the job in 6 hours.

Questions:
1. If Mark can finish the job in “m” hours, how long will it take Jessie to finish the job?
2. How would you represent the amount of work that Mark can finish in 1 hour? How about the
amount of work that Jessie can finish in 1 hour?
3. If the work together, what equation would represent the amount of work they can finish in 1
hour?
4. How would you describe the equation formulated in item 3?
5. How will you solve the equation formulated? What mathematics concept and principles are you
going to use?
ANSWER KEYS!!!
ACTIVITY 1:
1. x = 2
2. s = 5 or s = -2
3. r = 2 or r = -7
4. m = -2 or m = -1/2
5. p = -4/3 or p = -1
ACTIVITY 2:

5
2
2x  2 x 2  x  20 2 x 2  3x  3
1. 2. 3.
5x 5x 3x

x 1 x2  2
4. 5.
6x x 2  3x  2

ASSESSMENT:

1. x = -7 or x = 4

2. s = 0 or s = 6

3. t = 5 or t = 2

 1 17  1 17
4. x  or x 
2 2

19  161 19  161
5. x  or x 
2 2
ENRICHMENT:

1. ( m + 5 ) hours

1 1
2. ,
m m5
1 1 1
3.  
m m5 6
4. The equation formed is an algebraic equation.

5. The solution is 10 hours for Mark and 15 hours for Jessie.

REFERENCE!!!
 Mathematics Learner’s Material 9 (pages 77-87)
 http://www.jonblakely.com/wp-content/uploads/10_4.pdf

Prepared by:

LILIBETH G. GATOC

HINIGARAN NATIONAL HIGH SCHOOL

You might also like